FACTORS INFLUENCING THE CULTURAL INTELLIGENCE OF MUSLIM STUDENTS IN UNIVERSITIES IN SOUTHERN THAILAND - Thawornwongsa, Siwaporn; Noknoi, Chetsada (Journal of MCU Nakhondhat, 2026)
This study aimed to: 1) Investigate the factors influencing the cultural intelligence of Thai Muslim students, and 2) Propose guidelines for developing cross-cultural business learning that are appropriate for the context of students in Southern Thailand. A mixed-methods research design was employed. The quantitative phase collected data from 400 Thai Muslim undergraduate students enrolled in business-related programs at universities in Southern Thailand using a multistage sampling technique. Data were analyzed using descriptive statistics and multiple regression analysis. The qualitative phase involved in-depth interviews with 10 key informants, and the data were analyzed using content analysis. The findings revealed that the students reported high levels of religious identity, university support, cross-cultural experience, cultural adaptation, and cultural intelligence, with religious identity showing the highest mean score ( = 4.47, S.D. = 0.54). Multiple regression analysis indicated that cultural adaptation was the strongest predictor of cultural intelligence ( = .32), followed by university support ( = .27), cross-cultural experience ( = .25), and religious identity ( = .12). Together, these variables explained 55.1% of the variance in cultural intelligence (R² = .551). The qualitative findings identified five key approaches to enhancing cross-cultural business learning: 1) Promoting the preservation of religious identity, 2) Strengthening students' cultural adaptation through collaborative learning with peers from diverse cultural backgrounds, 3) Developing intercultural communication and teamwork skills, 4) Addressing challenges arising from cultural misunderstandings, and 5) Enhancing the role of universities in fostering cultural intelligence. The findings suggest that the development of cultural intelligence should be systematically promoted at the individual, instructional, and institutional levels to prepare graduates with cross-cultural business competencies for multicultural workplaces and the digital economy.